Oral Health Care in Infants and Deciduous Dentition: A Review (Indian Journal of Forensic Medicine & Toxicology, 2020)
Oral health goes in a close relationship with the general health. Hence, bad oral health affects the personallife and the lifestyle too. It affects interpersonal relationships, concentration, and productivity. Hence,maintenance of oral health, not only maintains the oral cavity, but, also helps maintain a quality life. Theprocess should start right from the prenatal period (oral care of the pregnant mother) and infancy. It has beenfound from surveys that the presence of dental caries in school going children affects their education as theytend to miss school due to pain and aesthetics.
Keywords: Oral Health, Maintenance, Oral Hygiene.